The Codelivery of siRNA and QDs by pH-Responsive Micelle for Hepatoma Cancer Cells - Cao, Zhonglin; Xiao, Huiyu; Li, Li; Liu, Maixian; Lin, Guimiao; Zhai, Peng; Yong, Ken-Tye; Wang, Xiaomei; Xu, Gaixia (Frontiers in Pharmacology, 2019)
Recently, RNA interfering (RNAi) has become a promising approach for cancer therapy. However, the application of RNAi for clinics is still hindered due to the lack of safe and efficient carriers. In this study, a pH responsive micelle based on polycaprolactone-block- poly 2-(dimethylamino)ethyl methacrylate (PCL-PDEM) cationic copolymer was developed to carry short interfering RNA (siRNA) for silencing interleukin-8 (IL-8) gene in hepatoma cancer cells. The transfection efficiency of the PCL-PDEM-siRNA/QDs nanoplex has reached about 70% and the expression level of IL-8 decreased about 63%. Furthermore, the co-delivery of quantum dots (QDs) and siRNA has been realized, which is beneficial to visualize the process of siRNA delivery. No considerable cytotoxicity from the nanoparticles has been observed, indicating that our responsive cationic micelle is potential in clinical trial for hepatoma cancer therapy.